2006
DOI: 10.1111/j.1440-1843.2006.00790.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrapleural cisplatin and OK432 therapy for malignant pleural effusion caused by non‐small cell lung cancer

Abstract: Although chest tube drainage took longer because of the time required for multiple administration of the agents, intrapleural combination therapy with cisplatin and OK432 was more effective in controlling malignant pleural effusions due to non-small cell lung cancer than monotherapy with either agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 35 publications
2
23
0
1
Order By: Relevance
“…In this study, although drug-induced side effects such as nausea, vomiting/anorexia, bone marrow depression, and pyrexia were observed, the incidence and extent of toxicity were similar in both groups, suggesting that hyperthermotherapy played no role in worsening side-effects, while improving the therapeutic efficacy. Similar results were reported in another study [10].…”
Section: Quality Of Life Scores and Adverse Events After Treatment Tsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, although drug-induced side effects such as nausea, vomiting/anorexia, bone marrow depression, and pyrexia were observed, the incidence and extent of toxicity were similar in both groups, suggesting that hyperthermotherapy played no role in worsening side-effects, while improving the therapeutic efficacy. Similar results were reported in another study [10].…”
Section: Quality Of Life Scores and Adverse Events After Treatment Tsupporting
confidence: 92%
“…Evidence from numerous clinical trials has demonstrated that therapeutic efficacy improved when cisplatin was used in combination with OK-432 [10,18]. For example, Ishida et al [10] reported that intrapleural low-dose cisplatin and OK-432 showed remarkable therapeutic efficacy with significantly lower rates of pleural effusion recurrence compared to either therapy alone, although the combination required a greater number of days for chest tube drainage because of the repeated administration of agents [10]. This result suggested that not only cytotoxic, but also sclerosing effects of the therapeutic agents in the pleural cavity were responsible for the control of MPE.…”
Section: Intrapleural Treatment Of Malignant Pleural Effusion mentioning
confidence: 98%
See 1 more Smart Citation
“…A single‐centre, randomized study from Japan compared the efficacy of cisplatin, OK‐432, or combination of both, as pleurodesing agents. Given intrapleurally, the combination of cisplatin and OK‐432 provided a significantly higher success rate of 86% than intrapleural administration of either agent alone (35% and 47%, respectively) in patients with malignant effusions from lung cancer 35 . From India, Agarwal et al .…”
Section: Pleural Diseasesmentioning
confidence: 99%
“…In one study, administration of a combination of OK-432 and 30 mg doxorubicin resulted in complete control of effusion for 80 % of patients [35]. In another study, a combination of OK-432 and cisplatin resulted in complete control of effusion for 180 days in 87 % of 15 patients whereas OK-432 by itself resulted in control in only 47 % of 17 patients [36]. In a recent study [37] of 75 patients with malignant effusions due to breast cancer, overall success was only 70.5 %.…”
Section: Ok-432mentioning
confidence: 99%